Lysis Buffers for Detecting Pork Content in Food Products - Khoiriah, Ulfah Lailatul; Baydillah, Pramudja; Darmawan, Raden; Nasori, Nasori; Taufany, Fadlilatul; Gunawan, Setiyo (Indonesian Journal of Chemistry, 2025)
The increasing number of counterfeit processed food products with non-halal ingredients, such as pork, has caused public concern about the halalness of Indonesian food products, especially in the Muslim community. This issue has prompted the development of halal authentication techniques, including deoxyribonucleic acid (DNA) isolation followed by polymerase chain reaction (PCR) amplification to detect pork DNA. The main purpose of this research was to modify the lysis buffer using tris-ethylenediaminetetraacetic acid, cetyl trimethylammonium bromide, salt, alkaline, and urea. Two DNA extraction methods were evaluated using kit-based and conventional methods with modified lysis buffer. Using a fluorometer, it was proven that the conventional method with modified urea lysis buffer produced quite competitive DNA concentrations (119 ng for pork meat and 100.05 ng for pork sausage), as confirmed by real-time PCR analysis. As a result, the modified urea lysis buffer can be further developed because it is more affordable.